PENGGUNAAN MEDIA POWER POINT BERBASIS ONLINE SEBAGAI DAMPAK PANDEMI COVID-19 KELAS IX DI SMP N 1 KUTASARI, KABUPATEN PURBALINGGA - Rizki Hidayat, Rizki; Sunhaji, Sunhaji (Jurnal Tawadhu, 2022)
Learning activities at SMP N 1 Kutasari class IX are very dependent on the ability of the teacher when providing material. One of them is the use of learning media that can be used by teachers to convey messages from sources to students in a planned manner, so that the process of teaching and learning activities can be carried out efficiently and effectively. Learning media can be in the form of audio, visual, audio-visual and multimedia media. One of them is power point media. In the field of education, powerpoint is not only used for presentations, but can be used as an effective learning medium. This can make students more interested in learning, because power points can be made as attractive as possible by relying on a unique and creative display that has been previously created by the teacher. The results showed that, 1) Students paid more attention during the learning process because the learning model was more interesting, 2) Students remembered the material given by the teacher more, and 3) The teacher was easier to convey the material because it was arranged using presentation slides.